2016
DOI: 10.1101/069120
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exaggerated CpH Methylation in the Autism-Affected Brain

Abstract: The etiology of autism, a complex neurodevelopmental disorder, remains largely unexplained. Here, we explore the role of CpG and CpH (H=A, C, or T) methylation within autism-affected cortical brain tissue. While no individual site of methylation was significantly associated with autism after multi-test correction, methylated CpH di-nucleotides were markedly enriched in autism-affected brains (~2-fold enrichment at p <0.05 cut-off, p=0.002). These results further implicate epigenetic alterations in pathobiologi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Gene lists were sourced from the reported hits of each paper [6,12,[21][22][23][24][25][26][27][28][29][30][37][38][39][40][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103].…”
Section: Autism Gene Enrichmentmentioning
confidence: 99%
“…Gene lists were sourced from the reported hits of each paper [6,12,[21][22][23][24][25][26][27][28][29][30][37][38][39][40][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103].…”
Section: Autism Gene Enrichmentmentioning
confidence: 99%
“…Several candidate gene-based studies have shown altered epigenetic states associated with autism [13][14][15][16][17][18]. Genome-scale screens have identified changes in DNA methylation (DNAm) at specific CpG sites [19,20] as well as global changes in non-CpG methylation levels [21] in postmortem cerebral tissue from individuals with ASD relative to controls. Studies of cerebral cortex tissue has revealed genomic spreading of histone H3 lysine 4 methylation and histone H3 lysine 27 acetylation marks, away from the promoter region, among a subset of individuals with ASD compared to controls [22,23].…”
Section: Resultsmentioning
confidence: 99%
“…The ratio of male/female of the disorder is 4.5 to 1 (192). The concordance of ASD among identical twins is high, suggesting complex inheritance and etiologic role of genetic factors (193,194). A combination of genetic, epigenetic and environmental factors plays important roles in ASD pathogenesis.…”
Section: Dna Methylation In Autism Spectrum Disordermentioning
confidence: 99%